Holocene ecosystem and temperature development inferred from invertebrate remains in Zminje Jezero (Dinaric Alps, Montenegro) - Schmidhauser, Noé R. M. M.; Finsinger, Walter; Cagliero, Eleonora; Heiri, Oliver (Journal of Paleolimnology, 2024)
Lake Zminje Jezero (1535 m a.s.l.) in Montenegro was studied for chironomid and other aquatic invertebrate remains in a sediment sequence dating back to 12,000 calibrated 14C years before present (cal yr BP), providing, to our knowledge, the first lake-sediment record studied for chironomids and other associated chitinous aquatic invertebrate remains in the Dinaric Alps. Changes in chironomid and other invertebrate remains along the record make it possible to constrain changes of relevant environmental variables for aquatic invertebrates in the lake including temperature, oxygen availability, trophic status and water depth. The results suggest moderate changes in trophic conditions with chironomid assemblages indicating meso- to eutrophic conditions during the analysed interval. Invertebrate assemblages were typical for lakes with relatively high oxygen availability with a minor trend during the middle to late Holocene to conditions observed in lakes that are more hypoxic. A change in temperature is suggested in the earlier part of the record when the share of chironomid taxa adapted to warmer conditions increased, at the Younger Dryas to Holocene transition, whereas later no particularly pronounced shifts in temperature-sensitive taxa were observed. July air temperatures were estimated based on chironomid assemblages using a transfer function based on calibration data consisting of 117 lakes sampled in the Swiss Alps and northern Switzerland. The results suggest that temperatures rapidly increased by 5 °C at the onset of the Holocene (11,500 cal yr BP) leading to a relatively warm early to mid-Holocene and thereafter slightly decreased during the late Holocene. Reconstructed temperatures are discussed together with a previously published pollen record for our study site and are broadly consistent with other chironomid-based temperature reconstructions from Central, Eastern and Southern Europe. From ca. 3000 cal yr BP sedimentation rates increased and from ca. 500 cal yr BP onwards pollen data suggest that the vegetation and lake catchment were affected by human activities, possibly influencing chironomid and other invertebrate assemblages in the lake and thereby also reconstructed temperatures. Overall, our results show that combining analyses of chironomid and other invertebrate assemblages can provide valuable insights into long-term environmental changes and can provide temperature reconstructions for small mountain lakes in the Balkans, such as Zminje Jezero.